2020
DOI: 10.1177/1559325820968413
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic Acid Prevents Radiation-Induced Pulmonary Fibrosis Through Attenuation of ROS/MYPT1/TGFβ1 Signaling Via miR-19b-3p

Abstract: The mechanism of pulmonary fibrosis caused by irradiation remains obscure. Since rosmarinic acid (RA) have anti-oxidant and anti-inflammatory properties, we aimed to evaluate the effect of RA on the X-ray-induced lung injury. Male rats received RA (30, 60, or 120 mg/kg) 7 days before 15 Gy of X-ray irradiation. Here, we showed that RA reduced X-ray-induced the expression of inflammatory related factors, and the level of reactive oxygen species. RA down-regulated the phosphorylation of nuclear factor kappa-B (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Zhang et al observed that RA (120 mg/kg) could regulate NF-κB signaling and the RhoA/Rock pathway through microRNA-19b-3p, which were responsible for the alleviation of inflammatory reactions, the reduction in collagen hyperplasia, and the suppression of pulmonary fibrosis development in the X-ray irradiation-induced rat model. Thus, RA is believed to be a potential alternative to attenuating radiotherapy-caused pulmonary fibrosis [ 275 ].…”
Section: Pharmacologymentioning
confidence: 99%
“…Zhang et al observed that RA (120 mg/kg) could regulate NF-κB signaling and the RhoA/Rock pathway through microRNA-19b-3p, which were responsible for the alleviation of inflammatory reactions, the reduction in collagen hyperplasia, and the suppression of pulmonary fibrosis development in the X-ray irradiation-induced rat model. Thus, RA is believed to be a potential alternative to attenuating radiotherapy-caused pulmonary fibrosis [ 275 ].…”
Section: Pharmacologymentioning
confidence: 99%
“…Our previous study have shown that RA can alleviate RIPF in rats [9], and it is recognized that FMT plays a core role in the pathogenesis of organ brosis [18]. In the present study, we further evaluated the effect of RA on RIPF and FMT in C57BL/6 mice.…”
Section: Ra Prevented Ripf and Inhibited The Progression Of Fmtmentioning
confidence: 84%
“…The enzymes superoxide dismutase, catalase, and heme oxygenase 1 are relevant for antioxidant defense in most cells exposed to oxygen [10,31]. Most recent studies also demonstrated the RA potential against radiation [29,[32][33][34][35][36]]. Bispo, for example, investigated the association of RA with octyl p-methoxycinnamate and avobenzone, showing an improvement in the in vivo SPF, although this bioactive compound was not able to enhance the photostability of that system [36].…”
Section: Discussionmentioning
confidence: 99%